Comparison of Letrozole vs Clomiphene Citrate for induction of ovulation in polycystic ovarian syndromeAn Iraqi study - Dr. Sama Mohammed Ali; Dr. INAS FADHIL ABDULHUSSEIN; Dr. Suhair Neima Kazom (Zien Journals, 2024)
Polycystic ovary syndrome is a common endocrine disorder in young women and manifests as infertility in 55-75%. Clomiphene citrate is still the standard drug for inducing or augmenting ovulation. It is not, however, equally successful in all situations. L Metromile is an aromatase inhibitor and is one of the alternative treatments to Clomiphene. This study aims to answer the question (does letrozole add anything to the art Of ovulation induction and represent a real alternative to Clomiphene? To compare the effects of letrozole (5 mg) and clomiphene citrate (100 mg) for ovulation induction in women with polycystic ovary syndrome. A prospective randomized trial study was done at Tikrit Teaching Hospital. The study comprised a total of 40 infertile women with polycystic ovary syndrome; Patients were randomized to treatment with 5 mg Of letrozole daily (20 patients) or 100 mg of clomiphene citrate daily (20 patients) for 5 days starting on day 3 Of menses. Timed intercourse was advised 24-36 hours after hCG injection. Then, both groups were followed by sonography every other day from day 10 Of the menstrual cycle for the number and size Of follicles and endometrial thickness were assessed. The study revealed that the C . C group induce ovum with size > 18mm 12 (60%) versus 17 (85%) among Letrzol group, while < 18mm in about 8 C.C group as compared with 3 (15%) in Letrzol group, this relation was statistically not significant. The study revealed that C.C group induce > 1 follicle 8 (40%) versus 2 (10%) among Letrzol group, while I follicle induced in about 6 (30%) in C.C group as compared with 16 (80%) in Letrzol group, this relation was statistically significant. The endometrium thickness was 4-5 mm in 14 (70%) among C.C group, and 17 (85%) in Letrzol group , while uterine thickness was 6-9.5mm in 6 (30%) among C.C group and 3 (15%) among Letrzol group, this relation was statistically not significant, study conclude that Letrozole should be considered as first line drug to get away from clomiphene's unwanted effects like thin endometrium and multifolliculogesis.
Keywords: letrozole; endometrium; clomiphene citrate; ovulation